Genetic diversity of cowpea (Vigna unguiculata L. Walp) landraces suggests Central Mozambique as an important hotspot of variation - Gomes, Ana Maria Figueira (2021)
Cowpea is a multiple-purpose drought-tolerant leguminous pulse crop grown in several dry tropical areas. Its domestication center is thought to be East or West Africa, where a high level of genetic diversity is apparently still found. However, detailed genetic information is lacking in many African countries, limiting the success of breeding programs. In this work, we assessed the genetic variation and gene flow in 59 Vigna unguiculata (cowpea) accessions from 10 landraces spanning across six agro-ecological zones of Mozambique, based on nuclear microsatellite markers. The results revealed the existence of high genetic diversity between the landraces, even in comparison to other world regions. Four genetic groups were found, with no specific geographic pattern, suggesting the presence of gene flow between landraces. In comparison, the two commercial varieties had lower values of genetic diversity, although still close to the ones found in local landraces. The high genetic diversity found in Mozambique sustains the importance of local genetic resources and farm protection to enhance genetic diversity in modern varieties of cowpea worldwide